2023
DOI: 10.1038/s41581-023-00699-9
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of distal renal tubular acidosis

Abstract: The kidneys have a central role in the control of acid-base homeostasis owing to bicarbonate reabsorption and production of ammonia and ammonium in the proximal tubule and active acid secretion along the collecting duct. Impaired acid excretion by the collecting duct system causes distal renal tubular acidosis (dRTA), which is characterized by the failure to acidify urine below pH 5.5. This defect originates from reduced function of acid-secretory type A intercalated cells. Inherited forms of dRTA are caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 229 publications
0
23
0
Order By: Relevance
“…In comparison, these injuries were markedly attenuated by RosA-Mn NPs treatment, confirming the potential ability of RosA-Mn NPs to protect against renal damage (Figure h). Excessive apoptosis of renal tubular epithelial cells and subsequent impairment of tubular repair have been reported to contribute to tubulointerstitial injury . Renal tubular cell apoptosis was determined by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, these injuries were markedly attenuated by RosA-Mn NPs treatment, confirming the potential ability of RosA-Mn NPs to protect against renal damage (Figure h). Excessive apoptosis of renal tubular epithelial cells and subsequent impairment of tubular repair have been reported to contribute to tubulointerstitial injury . Renal tubular cell apoptosis was determined by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL).…”
Section: Resultsmentioning
confidence: 99%
“…Excessive apoptosis of renal tubular epithelial cells and subsequent impairment of tubular repair have been reported to contribute to tubulointerstitial injury. 35 Renal tubular cell apoptosis was determined by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL). The fluorescence images and their quantification showed that the proportion of TUNEL positive cells in the CDDP-treated kidney tissue of AKI mice was much higher than that in the kidneys of mice treated with RosA-Mn NPs (see Figures 4h and 4f).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…H 1 -ATPase Activity is Decreased at the Basolateral Side of Non-Type A ICs Despite an Increased Basolateral Accumulation of the B2 Subunit The absence of the B1 subunit in type A ICs is partly compensated by enhanced abundance of the B2 isoform, which however fails to support stimulation of H 1 -ATPase activity by acidosis or angiotensin II. 22,23,25,26 Immunohistochemistry on kidneys from alkali-loaded mice showed diffuse staining for the B2 subunit toward the basolateral membrane of pendrin-positive ICs in Atp6v1b1 1/1 and a stronger and more pronounced basolateral B2 staining in pendrin-positive ICs in Atp6v1b1 2/2 mice (Figure 4, A and B, and Supplemental Table 6). Thus, we assessed whether basolateral H 1 -ATPase activity, necessary for proton reabsorption and bicarbonate secretion by non-type A IC, is affected by Atp6v1b1 gene deletion.…”
Section: Pendrin Activity Is No Longer Stimulated By Camp In the Abse...mentioning
confidence: 97%
“…17,20,21 Mutations in the gene encoding the B1 subunit (ATP6V1B1) cause distal renal tubular acidosis (dRTA) in man, characterized by the inability of the distal nephron to appropriately acidify the urine. 19,22 A mouse model deficient for the Atp6v1b1 gene showed impaired H 1 secretion by type A ICs in the CD. 23,24 Moreover, in the absence of the B1 subunit, the B2 subunit is upregulated in type A ICs and assumes a more apical localization.…”
Section: Introductionmentioning
confidence: 99%
“…As host defense mechanisms in the bladder are evaded, UPEC can reach the collecting duct (CD). The CD contains a salt-and-pepper, highly plastic epithelium 8 that is composed of two major cell types: intercalated cells (ICs) and principal cells (PCs) (Figure 1). Aquaporin-2-expressing cells serve as precursors for PCs, and IC subtypes and their differentiation is regulated by forkhead box protein I1 (Foxi1) transcription factor and JAG1 and NOTCH1/2 signaling.…”
Section: Intercalated Cells In the Collecting Ductsmentioning
confidence: 99%